Development of an activatable far-red fluorescent probe for rapid visualization of hypochlorous acid in live cells and mice with neuroinflammation - Mi, Long; Niu, Changhe; Chen, Jianqiang; Han, Feng; Ji, Xueying (Frontiers in Chemistry, 2024)
Recent investigations have suggested that abnormally elevated levels of HOCl may be tightly related to the severity of neuroinflammation. Although some successes have been achieved, fluorescent probes with far-red fluorescence emission and capable of detecting HOCl with high specificity in pure aqueous solution are still urgently needed. Herein, a responsive far-red fluorescent probe, DCI-H, has been constructed to monitor HOCl activity in vivo and in vitro. DCI-H could rapidly respond to HOCl within 120 s and had a low detection limit for HOCl of 1.5 nM. Importantly, physiologically common interfering species, except for HOCl, did not cause a change in the fluorescence intensity of DCI-HOCl at 655 nm. The results of confocal imaging demonstrated the ability of DCI-H to visualize endogenous HOCl produced by MPO-catalyzed H2O2/Cl -and LPS stimulation. With the assistance of DCI-H, upregulation of HOCl levels was observed in the mice model of LPS-induced neuroinflammation. Thus, we believed that DCI-H provided a valuable tool for HOCl detection and diagnosis of inflammationrelated diseases.